2013
DOI: 10.21273/hortsci.48.8.1010
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Cherry Fruit Firmness and Postharvest Quality of Late-maturing Cultivars Are Improved with Low-rate, Single Applications of Gibberellic Acid

Abstract: Sweet cherry (Prunus avium L.) producers in the Pacific Northwest have devoted considerable acreage to late-maturing cultivars. By using these cultivars to extend the harvest window, producers avoid lower returns associated with cherries harvested during the peak period (i.e., midseason) when supplies are overly abundant. Over several years, we evaluated preharvest applications of gibberellic acid (GA3) between 10 and 100 ppm (a.i.) on the late-maturing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Spraying 'Alyanak' apricot with 25 ppm BA + GA 4+7 and 100 ppm BA improved the fruit firmness. The role of GA in improving fruit firmness in this study is in accordance with the findings of the other researchers (Canli and Orhan, 2009;Einhorn et al, 2013;Facteau, 1986;MacDonald, 2002, 2007;Kupferman, 1989;Lenahan et al, 2006;Zhang and Whiting, 2011). Preharvest application of 25 ppm GA 3 is a routine treatment in cherry production used to increase the firmness of fruit (Canli and Orhan, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Spraying 'Alyanak' apricot with 25 ppm BA + GA 4+7 and 100 ppm BA improved the fruit firmness. The role of GA in improving fruit firmness in this study is in accordance with the findings of the other researchers (Canli and Orhan, 2009;Einhorn et al, 2013;Facteau, 1986;MacDonald, 2002, 2007;Kupferman, 1989;Lenahan et al, 2006;Zhang and Whiting, 2011). Preharvest application of 25 ppm GA 3 is a routine treatment in cherry production used to increase the firmness of fruit (Canli and Orhan, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…After harvest, softening of the apricot fruit adversely affects its marketability and value. GA 3 treatments in sweet cherry delayed fruit ripening (Andrews and Shulin, 1995;Canli and Orhan, 2009;Choi et al, 2002;Demirsoy and Bilgener, 2000;Horvitz et al, 2003;Kappel and MacDonald, 2002;Usenik et al, 2005;Webster et al, 2006) and increased fruit firmness (Canli and Orhan, 2009;Choi et al, 2002;Einhorn et al, 2013;Kappel and MacDonald, 2002). Delayed fruit ripening enabled fruit to stay on trees longer resulting in increased fruit size and fruit firmness (Ju et al, 1999).…”
mentioning
confidence: 99%
“…Figure 2 shows that nCeO 2 at 50 mg/L and bCeO 2 at 200 mg/L significantly reduced fruit firmness. Pulp texture is an important food quality characteristic (Ferris et al, 1999), which can be affected by fruit variety, gibberellic acid, and storage time, among others ( Zaller, 2007;Einhorn et al, 2013;Bink et al, 2014). More studies are needed in order to understand the effects ENPs on fruit firmness.…”
Section: Effects Of Treatments On Cucumber Yield and Fruit Qualitymentioning
confidence: 99%
“…Both in vitro and in vivo studies have demonstrated that cherry consumption is correlated with a reduction of several diseases, including cancer, cardiovascular, diabetes and other inflammatory diseases, as a result of a decrease in oxidant stress, inflammation, tumour suppression and glucose control . In recent years, different preharvest strategies have been carried out aiming to increase the quality attributes of cherry fruit at the time of harvest, such as gibberellic acid and oxalic acid, with the main effects being fruit with higher size, weight and firmness, and with the oxalic acid treatment also leading to increases in total anthocyanins, total phenolics and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%